Medical expulsive therapy: a cost effective evidence-based definitive treatment for ureteric stones - Ali, Qutubuddin; Khan, Shehtaj; Patel, Gambhir; Jaiswal, Kritik; ., Krishnanand (International Surgery Journal, 2020)
Background: The lifetime risk of kidney stones is between 5% and 10% and rates of recurrence are as high as 50%. Majority of the ureteric stones (70%) are found in the lower third of the ureter. Available setup, type, size of the stone, and expertise of the surgeon are the major factors affecting the treatment modality. Medical expulsive therapy has shown promising results in previous studies. Aim of the study was to assess the efficacy of tamsulosin and deflazacort combination therapy for stone expulsion in relation with site and size of stones. Methods: A total of 97 patients with ureteric calculi of size 10 mm or less attending the urology out-patient department were included. Received medical expulsive therapy using tamsulosin (0.4 mg) and deflazacort (30 mg) for 7 days. Patients were evaluated for stone expulsion on 7th day by non-contrast computed tomography of kidney ureter bladder. Site, side and size of stones were noted. Results: Ureteric calculi was more prevalent in the age group of 21-30 years 38 (39.2%). Male preponderance was observed (76.28%) with male female ratio being 3.2:1. Lower site 64 (65.97%) ureteric calculi were most common. The majority had a stone size of 4-6 mm (42%). Stones were expelled on 7th day in 69 (71.13%) patients. Expulsion rates were highest for the stone size of 2-4 mm (94.4%) followed by 4-6 mm (88.1%). The highest expulsion rates were observed for Lower ureteric stones (84.4%). Conclusions: Medical expulsive therapy using tamsulosin and deflazacort is an effective treatment modality for the management of ureteric stones, especially those present in lower ureter and those ≤8 mm in size.